Team Coordination Dynamics Measurement in Enroute Care Training: Defining Requirements and Usability Study. Issue 1 (October 2022) - Winner, Jennifer; King, Jayde; Gorman, Jamie; Grimm, David
Prior research indicates a need for objective and reliable measures of team communication and coordination. This need rings true for United States Air Force (USAF) teams, whose instructors heavily employ subjective evaluations within fast-paced training. Instructors must observe a multitude of teams and their communications, leaving room for varied evaluations and missed opportunities for feedback. Recent studies have advanced and tested team coordination measures based on dynamical systems theory, yielding results that illustrate the relationship between team communication flow and performance. This work leverages those measures and applies them in the context of USAF medical training. In this study, we assess the usability of a Team Dynamics Measurement System prototype. Users (n = 4) completed 15 tasks and evaluated system usability, perceived mental effort, system satisfaction, and task difficulty. Results indicate marginally acceptable overall system usability. These results helped identify essential interface modifications for future iterations. Future work and use cases for instructor support are discussed.